PTU-076 Myendoscopy. co.uk, an online resource for patients undergoing endoscopy. Issue 2 (June 2019) - Serna, Solange; Verma, Ajay
Abstract : Introduction: Prior to an endoscopy procedure, consent has to be sought from the patient. For consent to be valid, it must be voluntary, informed, and the person consenting must have the capacity to make the decision. The BSG Guideline for obtaining valid consent for gastrointestinal endoscopy procedures, recommends; " written information should be provided in advance of the procedure with sufficient time for the patient to read, evaluate and seek further information if required ". 1 The General Medical Council's consent guidance states: " Before accepting a patient's consent, you must consider whether they have been given the information they want or need, and how well they understand the details and implications of what is proposed. " 2 To meet these regulatory requirements, endoscopy units give information to patients via printed leaflets, to outline; what to expect, what is involved, what preparation is required, and the benefits & risks. This gives sufficient information for a patient to give informed consent. Information provided via an online platform would also meet regulatory requirements and may be preferred by many patients. An internet search shows that there is an NHS web resource for endoscopy which provides basic information, with limited media (a few images, no videos). 3 Images and videos of endoscopy procedures are abundant online but there is limited resources for patients that combines the detail of a pre-procedure information leaflet, with illustrative media. Methods: Using the current printed information resources for patients used at Kettering General Hospital (KGH), this information was transferred onto a webpage, and was illustrated with media taken from KGH's endoscopy unit. Results: In February 2019, a website was published: www.myEndoscopy.co.uk This website has a generic web address, minimal KGH branding, and is designed to be used by any patient undergoing a Gastroscopy, Sigmoidoscopy, or Colonoscopy (not just for KGH patients). It is accessible on PCs, laptops, tablets, and smartphones. The website has been promoted as a resource via direct email to colleagues across the UK, and via Social Media. Conclusion: This web resource is a big step forward in providing information to patients prior to having an endoscopic procedure. It has been designed to use generically by any patient irrespective of which hospital they are having their procedure. It has built in features to allow users to rate the website with comments so that we can evolve the content to meet the patient's needs. Over time, we will add more media, and information on ERCP, and capsule endoscopy. References: S M Everett, H Griffiths, U Nandasoma, et al . Guideline for obtaining valid consent for gastrointestinal endoscopy procedures. Gut 2016;0:1–17. doi:10.1136/gutjnl-201–11904 https://www.gmc-uk.org/ethical-guidance/ethical-guidance-for-doctors/consent https://www.nhs.uk/conditions/endoscopy/